Measuring China's income disparity using Theil-L index. - Su, Juanna Jielin. (2008)
This paper proposes an aggregate measure of income inequality for China, using data from household samples covering 29 provinces and over a period of 13 years, from 1993 to 2005. Applying the methodology of Theil-L index, the paper aggregates the income inequality at national level and decomposes it into inter-provincial and intra-provincial (rural-urban) level. Results have shown that intra-provincial income inequality contributed a major proportion to the overall inequality as compared to inter-provincial income inequality in China.